The Relationship between Perceived Stress and Breastfeeding Pattern among Primiparous Mothers: A Cross-sectional Study in the West of Iran - Ensiyeh Jenabi; Salman Khazaei; Arshia Nazari; Erfan Ayubi; Sara Abdoli (Iranian Journal of Nursing and Midwifery Research)
Background: The breastfeeding pattern of mothers in different societies has its roots in different social and cultural issues. Recognizing the significance of this issue and the absence of similar research in the western region of Iran, this study explored the relationship between perceived stress and breastfeeding patterns among primiparous mothers. Materials and Methods: This cross-sectional study was conducted on 269 mothers from January to May 2023 in the city of Hamadan, Iran. The demographic and midwifery information questionnaire and the perceived stress scale (PSS) were used. Data analysis was performed using Stata software, with the significance level set at 0.05. Results: In the present study, only 24.16% of breastfeeding mothers breastfed exclusively. The findings showed that with each unit increase in the perceived stress score, the chance of not exclusively breastfeeding increased by 54%. Moreover, with each year of increase in the mother’s age, the chance of not exclusively breastfeeding decreased by 15%. Conclusions: The results showed a negative association between stress and exclusive breastfeeding. Therefore, it is recommended that mental health promotion be incorporated into policy-making and planning for maternal and neonate healthcare to ensure the continuation of exclusive breastfeeding.